DEFINITIONS: DOES DISJUNCTION MEAN DYSFUNCTION? - Kingsburry, Justine; McKeown-Green, Jonathan (Journal of Philosophy, 2009)
The article discusses definitions that are disjunctive or the definition of things of interest that does not provide all one might want from a definition. It talks on the four features of a definition such as extensional adequacy, criterial adequacy, conjunctiveness, and motivational adequacy. It cites spouse as an example of disjunctive definition as well as the many definitions of art. It also notes the types of disjunctive definitions including the recursive sort.